2021
DOI: 10.3389/fnins.2021.671767
|View full text |Cite
|
Sign up to set email alerts
|

Neurosensory Prosthetics: An Integral Neuromodulation Part of Bioelectronic Device

Abstract: Bioelectronic medicines (BEMs) constitute a branch of bioelectronic devices (BEDs), which are a class of therapeutics that combine neuroscience with molecular biology, immunology, and engineering technologies. Thus, BEMs are the culmination of thought processes of scientists of varied fields and herald a new era in the treatment of chronic diseases. BEMs work on the principle of neuromodulation of nerve stimulation. Examples of BEMs based on neuromodulation are those that modify neural circuits through deep br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 149 publications
0
5
0
Order By: Relevance
“…In addition, the selectivity of bioelectronics as a sensor for disease biomarkers can be improved by using various types of bioreceptors, such as antibodies, aptamers, and peptides/proteins, improving the potential for bioelectronic systems to be applied to healthcare 132–139 . Last, the mixture of gases and vapors of human breath has potential as a completely noninvasive and safe target for health diagnosis and monitoring 140,141 . By detecting volatile biomarkers present in the breath, follow‐up for a patient's health can be assessed 9 …”
Section: Wearable and Implantable Bioelectronic Systems For Smart Hea...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the selectivity of bioelectronics as a sensor for disease biomarkers can be improved by using various types of bioreceptors, such as antibodies, aptamers, and peptides/proteins, improving the potential for bioelectronic systems to be applied to healthcare 132–139 . Last, the mixture of gases and vapors of human breath has potential as a completely noninvasive and safe target for health diagnosis and monitoring 140,141 . By detecting volatile biomarkers present in the breath, follow‐up for a patient's health can be assessed 9 …”
Section: Wearable and Implantable Bioelectronic Systems For Smart Hea...mentioning
confidence: 99%
“…[132][133][134][135][136][137][138][139] Last, the mixture of gases and vapors of human breath has potential as a completely noninvasive and safe target for health diagnosis and monitoring. 140,141 By detecting volatile biomarkers present in the breath, follow-up for a patient's health can be assessed. 9 2.1.4 | Bioelectronics in healthcare: Stimulation, actuation, and therapeutics Bioelectronic systems, especially implantable bioelectronics, have extensive applications in many diseases that are caused by dormant or aberrant neural networks.…”
Section: Bioelectronics In Healthcare: Biosensing and Diagnosticsmentioning
confidence: 99%
“…Bioelectronic devices also include devices that work on the principle of neuromodulation, which modify neural signals via deep-brain stimulation, vagus nerve stimulation, spinal nerve stimulation, and retinal and auditory implants [ 19 ]. Koopman et al reported that vagus nerve stimulation (VNS) inhibits tumor necrosis factor, an inflammatory molecule that is a major therapeutic target in rheumatoid arthritis (RA), and which attenuates disease severity [ 20 ].…”
Section: Opportunities and Limitations In Bioelectronic Devicesmentioning
confidence: 99%
“…These devices consist of a receiver, transmitting coil, and an electrode array that stimulate the retina to induce vision in patients with retinal degeneration [ 24 ]. Auditory implant types, such as cochlear implants and auditory brainstem implants (ABIs), have a neuromodulatory function [ 19 ]. Cochlear implants stimulate auditory nerve fibers via electrodes implanted in the cochlea to help patients with sensorineural hearing loss using functional auditory nerve fibers.…”
Section: Opportunities and Limitations In Bioelectronic Devicesmentioning
confidence: 99%
“…Bioresorbable and transient electronics, with tunable degradation properties, obviated potential adverse effects of chronic implants and the need for follow-up procedure ( 5 ). Despite the giant technological advances and the deployment of many devices in the clinical environment, there are still challenges to bridge the gap between the full potential of neuroelectronic interfaces and their translation into broad clinical practice ( 6 ). Major existing issues are related to methods that enable natural integration of electronic components into neuronal tissue, the timescale of activity, the long-term stability for extended recordings, which would ideally cover the entire adult life of animals, and the availability of models to test in vivo neurostimulation or neuromodulatory action of bioelectronic interfaces ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%